2018
DOI: 10.1063/1.5001928
|View full text |Cite
|
Sign up to set email alerts
|

Classical molecular dynamics simulation of microwave heating of liquids: The case of water

Abstract: We perform a complete classical molecular dynamics study of the dielectric heating of water in the microwave (MW) region. MW frequencies ranging from 1.0 to 15.0 GHz are used together with a series of well-known empirical force fields. We show that the ability of an empirical force field to correctly predict the dielectric response of liquids to MW radiation should be evaluated on the basis of a joint comparison of the predicted and experimental static dielectric constant, frequency-dependent dielectric spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 29 publications
(19 reference statements)
2
11
0
Order By: Relevance
“…The frequency-dependent dielectric constant can be calculated using the determined τ D through the following equation from the Debye relaxation model: ε normalR normale ( ω ) = ε + ε normals ε 1 + ω 2 τ normalD 2 ε normalI normalm ( ω ) = ( ε s ε ) ω τ normalD 1 + ω 2 τ normalD 2 where ε ∞ and ε s are the infinite frequency dielectric constant and static dielectric constant, respectively. It should be emphasized that all of the ε ∞ and ε s values employed in our calculation of these dielectric spectra are experimental values that were obtained from the literature. The corresponding values are presented in Table . In this Article, the frequency range of the frequency-dependent dielectric spectra is from 300 MHz to 300 GHz.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The frequency-dependent dielectric constant can be calculated using the determined τ D through the following equation from the Debye relaxation model: ε normalR normale ( ω ) = ε + ε normals ε 1 + ω 2 τ normalD 2 ε normalI normalm ( ω ) = ( ε s ε ) ω τ normalD 1 + ω 2 τ normalD 2 where ε ∞ and ε s are the infinite frequency dielectric constant and static dielectric constant, respectively. It should be emphasized that all of the ε ∞ and ε s values employed in our calculation of these dielectric spectra are experimental values that were obtained from the literature. The corresponding values are presented in Table . In this Article, the frequency range of the frequency-dependent dielectric spectra is from 300 MHz to 300 GHz.…”
Section: Results and Discussionmentioning
confidence: 99%
“…h i b i t e d .using the determined τ D through the following equation from the Debye relaxation model:31 …”
mentioning
confidence: 99%
“…We recently reported on classical MD simulations of the dielectric heating of liquid water using MW radiation at different frequencies 2 . We concluded that the capability of an empirical force field to correctly predict the dielectric response of liquids to MW radiation should be evaluated on the basis of a joint comparison of the predicted and experimental static dielectric constant, frequency-dependent dielectric spectra, and MW heating rates.…”
Section: Classical Molecular Dynamics (Md) Is a Very Powerful Atomistmentioning
confidence: 99%
“…The use of pure MEA liquid in CO 2 capture is not feasible because of the high viscosity of the product. However, the temperature required for CO 2 In Figure 1 we illustrate the molecular geometry of the MEA molecule. In this paper we care-fully evaluate the accuracy of most available empirical force fields of MEA, namely MEAa2007 8 , MEAo2007 8 , MEAa2015 9 , OPLS-aa 10 , OPLS-aam 10 , GROMOS-aa 11,12 , and GROMOS-ua 11,12 .…”
Section: Classical Molecular Dynamics (Md) Is a Very Powerful Atomistmentioning
confidence: 99%
See 1 more Smart Citation